First Evidence of Collective Human Inhumation from the Cardial Neolithic (Cova Bonica, Barcelona, NE Iberian Peninsula) - Oms, F. Xavier (2018)
Excavations at Cova Bonica (Barcelona, Spain) have revealed 98 human remains, grouped into five age clusters and corresponding to a minimum of six non-articulated individuals. The remains are clearly associated with Cardial pottery, lithic artifacts, and ornaments suggesting an Early Neolithic horizon. The radiocarbon dating of three human individuals provides a reliable attribution to this period, with a range between ca. 5470 and 5220 CAL B.C., identifying it as one of the few assemblages of human remains directly dated from this period. These remains correspond to a rare collective human inhumation and join a growing body of samples from the Cardial Neolithic, which is providing some of the important sites for the study of population movement and the spread of Neolithization along the western Mediterranean coast.